If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying fx = (400 + 20x)(90 + -1x) Multiply (400 + 20x) * (90 + -1x) fx = (400(90 + -1x) + 20x * (90 + -1x)) fx = ((90 * 400 + -1x * 400) + 20x * (90 + -1x)) fx = ((36000 + -400x) + 20x * (90 + -1x)) fx = (36000 + -400x + (90 * 20x + -1x * 20x)) fx = (36000 + -400x + (1800x + -20x2)) Combine like terms: -400x + 1800x = 1400x fx = (36000 + 1400x + -20x2) Solving fx = 36000 + 1400x + -20x2 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = 36000x-1 + 1400 + -20x Simplifying f = 36000x-1 + 1400 + -20x Reorder the terms: f = 1400 + 36000x-1 + -20x
| (3q-8)(-9q+2)(q-2)=0 | | -2x^2=12x-14 | | 5+3*4-8+2*7= | | 2[9(6-5)]= | | (14x+5)(14x+5)=20 | | 2(x+4)+star=16 | | 5f=f+36 | | 5x+5(2x+10)=10x+12 | | 2(x+4)-5x=23 | | 3x+2star+x=x+6 | | 5x-2=-x+7+6 | | 5(y+5)-5y=31 | | -3+sy=17 | | 8x-1x=7x | | 32-(2c+4)=2(c+7)+c | | ax+by+c+2ax-3by+c+by-c= | | 5=(7-2)/3-x | | 2x^2-13=7x | | 5=7-2/3-x | | 3(2star)-3star+4=2star+5 | | 4a+2b+c=8 | | 12-4(6x-2)=8-(2x+5) | | 35=5u | | 2x+6=7-3x | | 97=215t+-16t^2 | | y=sin(5x+2) | | 7w-16w= | | 6c=4c+6 | | 5(k-3)-8=5k-(4k-3) | | 4x+3-5x= | | 2x+80+145+x=360 | | -8g+4.5=36.3 |